Alternatif Strategi Pengembangan Usahatani Jamur Tiram Putih di Kabupaten Kotawaringin Barat: Alternative Strategy for White Oyster Mushroom Farming Development in West Kotawaringin Regency - Rizkiyah, Noor; Laily, Dona Wahyuning; Roidah, Ida Syamsu; Rozci, Fatchur; Sofiyah, Sofiyah; Purwanto, Eko (Jurnal Ilmiah Manajemen Agribisnis, 2024)
This study aims to identify internal and external factors, specifically the company's strengths, weaknesses, opportunities, and threats, to formulate strategies for business development. This research adopts a descriptive qualitative approach to analyze and interpret the data systematically. Data collection techniques include interviews with the company owner and employees, as well as direct observations at the company site. he strategy formulation process utilizes internal and external factors through a SWOT analysis. The SWOT analysis results yield IFAS and EFAS scores, which are further analyzed using the Internal-External (IE) matrix. Based on the findings, the recommended strategies for the company include market penetration, market development, product and technology development.